Development of High-Density SNP Markers and Their Application in Evaluating Genetic Diversity and Population Structure in Elaeis guineensis - Xia, Wei; Luo, Tingting; Zhang, Wei; Mason, Annaliese S.; Huang, Dongyi; Huang, Xiaolong; Tang, Wenqi; Dou, Yajing; Zhang, Chunyu; Xiao, Yong (Frontiers in Plant Science, 2019)
Abstract High-density single nucleotide polymorphisms (SNPs) are used as highly favored makers to analyze genetic diversity and population structure, to construct high-density genetic maps and provide genotypes for genome-wide association analysis. In order to develop genome-wide SNP markers in oil palm (Elaeis guineensis), SLAF-seq (Single Locus Amplified Fragment sequencing) technology was performed in a diversity panel of 200 oil palm individuals and 1 261 501 SNPs were identified with minor allele frequency > 0.05 and integrity > 1. Among them, only 17.81% can be mapped within the genic region and the remaining was located into the intergenic region. A positive correlation was detected between the distribution of SNP markers and retrotransposons (TEs). Population structure analysis showed that the 200 individuals of oil palm can be divided into five subgroups based on cross validation errors. However, the subpopulations divided for the 200 oil palm individuals based on the SNP markers were not accurately related to their geographical origins and 80 oil palm individuals from Malaysia showed highest genetic diversity. In addition, the physical distance of LD decay in the analyzed oil palm population was 14.516 Kb when r2 = 0.1. The LD decay distances for different chromosomes varied from 3.324 Kb (chromosome 15) to 19.983 Kb (chromosome 7). Our research provides genome-wide SNPs for future targeted breeding in palm oil.